Changing the main indicators to assess motor function in children with cerebral palsy spastic form by hydrokinesitherapy - Taran I.V (Kharkov National Pedagogical University, 2013)
The aim of the study is to identify the efficiency of the developed technique hydrokinetic system of physical rehabilitation for children 3-5 years old with cerebral palsy spastic form. Examined the impact of comparing the effectiveness of exercise in the water by two techniques: the author and accepted. In experiment involved 24 people aged 3-5 years old with cerebral palsy spastic form. The experiment lasted one year, classes were held hydrokinesitherapy 2 times a week. In the study recorded the performance evaluation of basic motor functions to the experiment, six months later, and after the experiment. It is shown that an important component of physical rehabilitation of patients is hydrokinesotherapy. Shows the direction of the development of motor skills of children 3-5 years old. Study of the development of indicators basic motor functions.